2019
DOI: 10.1111/1753-0407.12967
|View full text |Cite
|
Sign up to set email alerts
|

Dietary preferences and diabetic risk in China: A large‐scale nationwide Internet data‐based study

Abstract: Background Unhealthy diet is one of the important risk factors of diabetes, which is one of the major public health problems in China. The Internet tools provide large‐scale passively collected data that show people's dietary preferences and their relationship with diabetes risk. Methods 212 341 708 individuals' dietary preference labels were created based on Internet data from online search and shopping software. Metabolic data obtained from the 2010 China Noncommunicable Disease Surveillance, which had 98 65… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 20 publications
1
31
0
Order By: Relevance
“…Partly consistent with previous studies (Dovey et al 2016;Park et al 2017;He et al 2019), we found that spicy food consumption metrics, including frequency and pungency degree, were clustered with diverse factors, such as weekly tea/alcohol drinking, current tobacco smoking and different dietary habits. Several studies have recently reported the health effects of spicy food on various diseases (McCarty et al 2015;Chen et al 2017b;Zhao et al 2020). However, such associations could be modified by these lifestyle factors according to this study.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Partly consistent with previous studies (Dovey et al 2016;Park et al 2017;He et al 2019), we found that spicy food consumption metrics, including frequency and pungency degree, were clustered with diverse factors, such as weekly tea/alcohol drinking, current tobacco smoking and different dietary habits. Several studies have recently reported the health effects of spicy food on various diseases (McCarty et al 2015;Chen et al 2017b;Zhao et al 2020). However, such associations could be modified by these lifestyle factors according to this study.…”
Section: Discussionmentioning
confidence: 46%
“…However, such associations could be modified by these lifestyle factors according to this study. For example, a study only adjusted for age and sex found that spicy food preference was negatively correlated with diabetes prevalence (Zhao et al 2020), and another prospective study found the same result, but the result was found statistically insignificant after further adjustment for smoking, alcohol consumption, physical activity and BMI (Lv et al 2015). In addition, details of these lifestyle behaviours differed across spicy food intake frequency and pungency degree, which might affect health outcomes in different ways.…”
Section: Discussionmentioning
confidence: 98%
“…Kang et al found that different doses of CAP in the diet altered the gut microbiota of healthy subjects for two weeks. The results showed that CAP boosted the Firmicutes/Bacteroidetes ratio and the number of Faecalibacterium (Zhao et al, 2020). This suggests that CAP can regulate the composition of the microbiome, and several studies have shown that it can improve related diseases via regulation of microbes.…”
Section: Discussionmentioning
confidence: 82%
“…One's search queries related to food on the Internet could also be reflective of their dietary habits. Zhao et al (2019) conducted a correlation analysis between Chinese dietary preferences from Baidu search data and diabetes risk from government statistics and found a geographical distribution pattern. Besides, online food recipes have been recognized as a good source of Internet data to study recipe production, consumption, and innovation (Rong, Liu, Huo, & Sun, 2019).…”
Section: Dietary Pattern Characterizationmentioning
confidence: 99%